IMPLEMENTASI HAK RESTITUSI BAGI KORBAN KEKERASAN SEKSUAL ANAK: HAMBATAN DAN SOLUSI DALAM PERSPEKTIF VIKTIMOLOGI - Afrinda; Ahmad Lonthor; Fauzia Rahawarin; Syah Awaluddin; Ridwan Fauzi Lestaluhu; Husin Anang Kabalmay (TAHKIM, 2026)
This study aims to analyze the implementation of restitution rights for child victims of sexual violence and to identify obstacles and solutions from a victimological perspective. Although Law Number 12 of 2022 concerning Sexual Violence Crimes (UU TPKS) has provided normative reinforcement, the fulfillment of restitution rights in practice still faces significant obstacles. The research method used is normative legal research with a statutory and conceptual approach. The results indicate that the implementation of restitution is still far from ideal due to three main obstacles: normative obstacles related to the complexity of administrative procedures, structural obstacles in the form of law enforcement officials' lack of sensitivity in calculating losses, and substantial obstacles triggered by the perpetrator's financial inability. From a victimological perspective, the failure to execute restitution is a form of secondary victimization by the state. As a solution, this study recommends optimizing the role of the LPSK, activating the Victim Trust Fund mechanism as state compensation for indigent perpetrators, and implementing the seizure of the perpetrator's assets starting from the investigation stage to ensure the certainty of restoring the victim's rights Keywords: restitution, child sexual violence, victimology, victim recovery, UU TPKS